CONDUCT OF PROBATE PROCEEDINGS BY A NOTARY PUBLIC IN THE REPUBLIC OF SERBIA - Milović, Jovana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The introduction of the notary public service in the Serbian legal system has introduced a number of novelties in matters of inheritance law, among which the most important is the possibility of entrusting the procedure for discussing the inheritance to notaries public. Conducting court proceedings to deal with inheritance is a tradition in the Serbian legal system. Due to the above, it was not easy to interrupt her. Thus, the Serbian legislator still envisages the jurisdiction of the court to discuss the inheritance, with the possibility of entrusting this procedure to a notary public, when it deems that such an action is expedient. The author tries to determine the justification of entrusting the procedure to notaries through the studied practice of courts and notaries, by simultaneously examining the possibility of transferring competencies for conducting probate proceedings entirely to notaries. Determining the relief of the courts and reducing the time needed to complete the procedure for discussing the legacy will serve the achievement of the set goal.
Keywords: notaries; courts; probate proceedings; relieving courts; trial within a reasonable time